Efficacy of Autoinoculation in Treatment of Multiple Viral Warts - Akram, Ayesha; Fatima, Nighat; Amin, Saba; Safdar, Sohail (Biological and Clinical Sciences Research Journal, 2025)
Viral warts caused by human papillomavirus (HPV) are common and often resistant to conventional therapies. Autoinoculation therapy stimulates an immune response by reintroducing wart tissue into the skin, offering a potential, low-cost and effective alternative. This study evaluated the efficacy and safety of autoinoculation in treating multiple viral warts in the Pakistani population. Methods: A descriptive study was conducted in the Department of Dermatology, Ibn-e-Sina Hospital, Multan, from November 2023 to April 2024. Ninety-one patients aged 18–60 years with multiple warts underwent autoinoculation. Patients were followed for 12 weeks, and outcomes were classified as complete, partial, or no clearance. Data were analyzed using SPSS version 23, with chi-square tests applied for associations (p ≤ 0.05). Results: The mean age was 31.8 ± 10.4 years; 57.1% were females. After 12 weeks, 63.7% achieved complete clearance, 23.1% partial, and 13.2% no response. Higher efficacy was observed in younger patients (68.4%) and those with shorter disease duration (71.4%). Mild transient pain and erythema occurred in 17.6%, with no major complications or recurrences. Conclusion: Autoinoculation is a safe, simple, and effective method for managing multiple viral warts, achieving high clearance rates with minimal side effects. It is particularly valuable in resource-limited settings like Pakistan and may serve as an accessible alternative to conventional therapies. Further randomized trials are recommended to confirm long-term efficacy.